Nontuberculous mycobacterial infection of the knee after arthrocentesis for idiopathic hemarthrosis: A case report. (May 2021) - Moritake, Akihiro; Mori, Shigeshi; Kamiya, Masato; Yamazaki, Kenji; Aoyama, Shingo; Akagi, Masao; Togawa, Daisuke
Abstract: Introduction: Nontuberculous mycobacterial (NTM) infections of the musculoskeletal system are uncommon. Such infections are typically acquired by direct inoculation after penetrating trauma, surgical procedures, or needle injections. There are no reported cases of NTM infection after arthrocentesis for idiopathic hemarthrosis of the knee. Here we report a case of NTM infection in the knee that developed after arthrocentesis for idiopathic hemarthrosis of the knee. Presentation of case: The patient was an 85-year-old woman who experienced swelling of the left knee. An arthrocentesis was carried out, and hemarthrosis was found. The patient was referred to our hospital for repeated recurrence of hematoma of the knee. Significant swelling was observed in the suprapatellar sac. Magnetic resonance imaging examination revealed a mass at the suprapatellar sac. Laboratory data showed elevation of inflammatory markers. Debridement was performed under arthroscopy and samples were collected for culture. Although routine microbiological cultures were negative, the patient continued to experience knee swelling and laboratory data showed high C-reactive protein levels. Therefore, open debridement was carried out. At 4 weeks after the first surgical treatment, intraoperative cultures yielded Mycobacterium intracellulare . At this point, we diagnosed septic arthritis of the knee due to NTM infection. The patient showed an excellent prognosis with three-drug medical treatment for 1 year. Conclusion: Clinically, diagnosis of septic arthritis due to NTM infection is not easy. Because selection of examination depends on clinical suspicion, NTM infections should be considered for patients with elevation of inflammatory markers after episodes of surgical procedures, and/or needle injections. Highlights: ・Nontuberculous mycobacterial (NTM) infections of the musculoskeletal system are uncommon. ・A case of NTM infection in the knee that developed after arthrocentesis. ・NTM infections should be considered for patients with elevation of inflammatory markers after needle injections.